A Pathogenic Missense Variant (c.1617G>A, p.Met539Ile) in UBA1 Causing Infantile X-Linked Spinal Muscular Atrophy (SMAX2) - Wang, Xin Hua; Zhang, Lin Mei; Yang, Xue; Zhou, Shui Zhen (Frontiers in Pediatrics, 2020)
Background: Infantile X-linked spinal muscular atrophy (SMAX2) is a rare type of spinal muscular atrophy associated with UBA1 variants. Methods: Clinical imaging and neurophysiological tests were performed on a Chinese patient with SMAX2. Further, focused panel sequencing of UBA1 was carried out on samples of both the proband and his maternal relatives.Results: The proband, a 4-year-old boy with the SMAX2 phenotype, suffered from reduced exercise capacity since infancy. His other symptoms included speech difficulties, severe nasal tone, reduced distal muscle strength, areflexia, and inadequate sucking ability. The brain MRI of the proband's showed normal results but the electromyography results showed multiple peripheral neurogenic lesions. Five male members of the proband's family were affected with the SMAX2 phenotype. They presented similar symptoms and had experienced a long and autonomous life. Molecular analysis revealed a novel missense variant (c.1617G>A, p.Met539Ile) in the exon 15 of UBA1. The proband's mother, as well as grandmother, carried the heterozygous missense UBA1 variant; whereas, the male patients from the family carried the hemizygotic variant. Conclusions:The affected members in this Chinese family showed unique features such as extended life span, no fractures and cramps as compared with previously reported SMAX2 cases. The novel missense variant (c.1617G>A (p.Met539Ile) in UBA1 highlights the critical role of this gene in causing SMAX2 phenotype.